The effectiveness of protective measures against Streptococcosis and the immune responses triggered by the administration of live, live-attenuated, and killed vaccines were assessed in Nile tilapia (Oreochromis niloticus) - El-daim, Amira; Matter, Aya F.; Mohamed, Mona G.; Abdallah, Mona; Raslan, Walaa S.; Youssef, Hadeer A. (Journal of Advanced Veterinary Research, 2024)
The objective of this project was to develop live (LV), live attenuated (LAV), and autoclaved killed vaccines (AKV). The development of the vaccine involves utilizing two well-characterized strains of Streptococcus iniae (S. iniae), namely S. iniae 1 and S. iniae 2. S. iniae 2 was obtained from Department of Fish diseases, Faculty of Veterinary Medicine, Beni-Suef University, Egypt while S. iniae 1 strain was gifted from microbiology department, Egyptian Drug Authority, Dokki, Giza, Egypt. Pathogenicity test and lethal dose determination were performed. To conduct the experiment, apparently healthy Nile tilapia, Oreochromis niloticus (O. niloticus) of average weight 30Â±0.2g were divided into five experimental groups: T1 group, which served as a negative control and received saline; T2 group, which served as a positive control and received S. iniae 2; T3 group, which received an autoclaved killed vaccine for S. iniae 2; T4 group, which received a live attenuated vaccine for S. iniae 2; and T5 group, which received a live vaccine for S. iniae 1. At the end of the vaccination period, S. iniae 2 was introduced challenge to all groups. Serum samples were collected three weeks after vaccination to measure serum bactericidal activity, lysozyme activity, nitric oxide, alkaline phosphatase, and acid phosphatase. The findings demonstrated that the pathogenicity test reach 0 and 100% mortality rate for S. iniae 1 and S. iniae 2, respectively. Live attenuated vaccine had significantly higher protective rate than live vaccinations, while autoclaved vaccine had the best protective efficacy (88.2%). These results were confirmed through measurement some immune parameters as Serum bactericidal activity, lysozyme activity, nitric oxide, alkaline phosphatase and acid phosphatase.